Indications for islet or pancreatic transplantation: Statement of the TREPID working group on behalf of the Société francophone du diabète (SFD), Société francaise d’endocrinologie (SFE), Société francophone de transplantation (SFT) and Société française de néphrologie – dialyse – transplantation (SFNDT) - Wojtusciszyn, A.; Branchereau, J.; Esposito, L.; Badet, L.; Buron, F.; Chetboun, M.; Kessler, L.; Morelon, E.; Berney, T.; Pattou, F.; Benhamou, P.-Y.; Vantyghem, M.-C.; et al. (Diabetes & metabolism, 2019)
While either pancreas or pancreatic islet transplantation can restore endogenous insulin secretion in patients with diabetes, no beta-cell replacement strategies are recommended in the literature. For this reason, the aim of this national expert panel statement is to provide information on the different kinds of beta-cell replacement, their benefit-risk ratios and indications for each type of transplantation, according to type of diabetes, its control and association with end-stage renal disease. Allotransplantation requires immunosuppression, a risk that should be weighed against the risks of poor glycaemic control, diabetic lability and severe hypoglycaemia, especially in cases of unawareness. Pancreas transplantation is associated with improvement in diabetic micro- and macro-angiopathy, but has the associated morbidity of major surgery. Islet transplantation is a minimally invasive radiological or mini-surgical procedure involving infusion of purified islets via the hepatic portal vein, but needs to be repeated two or three times to achieve insulin independence and long-term functionality. Simultaneous pancreas-kidney and pancreas after kidney transplantations should be proposed for kidney recipients with type 1 diabetes with no surgical, especially cardiovascular, contraindications. In cases of high surgical risk, islet after or simultaneously with kidney transplantation may be proposed. Pancreas, or more often islet, transplantation alone is appropriate for non-uraemic patients with labile diabetes. Various factors influencing the therapeutic strategy are also detailed in this report.